2006
DOI: 10.1186/1471-2105-7-46
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and asymmetric divergence of duplicate genes in the human gene coexpression network

Abstract: Background: While gene duplication is known to be one of the most common mechanisms of genome evolution, the fates of genes after duplication are still being debated. In particular, it is presently unknown whether most duplicate genes preserve (or subdivide) the functions of the parental gene or acquire new functions. One aspect of gene function, that is the expression profile in gene coexpression network, has been largely unexplored for duplicate genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 51 publications
3
20
1
Order By: Relevance
“…For example, in multiple eukaryotic species, the expression correlation between a duplicate pair decreases as Ks increases [56], [63][65]. Similarly, the fraction of potential protein interaction partners (predicted based on co-expression) shared between a duplicate gene pair in human declines as Ks increases [34]. Therefore, it is not particularly surprising that the overall proportion of duplicates that lose stress responsiveness increases as Ks increases.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in multiple eukaryotic species, the expression correlation between a duplicate pair decreases as Ks increases [56], [63][65]. Similarly, the fraction of potential protein interaction partners (predicted based on co-expression) shared between a duplicate gene pair in human declines as Ks increases [34]. Therefore, it is not particularly surprising that the overall proportion of duplicates that lose stress responsiveness increases as Ks increases.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of newly duplicated genes experience a period of relaxed purifying selection, while only a relatively small proportion exhibits a signature of positive selection consequent to the acquisition of new biological functions [66]. Presumably, in between the initial post-duplicational redundancy and eventual neofunctionalisation through genetic divergence, there is a 'half-way house' state in which a gene is relatively free to explore the acquisition of new functions while still being constrained to some extent by selection against the loss of those functions it has already acquired [67]. …”
mentioning
confidence: 99%
“…Previous studies have shown that the retention of duplicate genes can result in rapid divergence in expression patterns (Farre & Alba, 2010;Ganko, Meyers, & Vision, 2007;Gu, Nicolae, Lu, & Li, 2002;Leite et al, 2018) and is often asymmetric (Chung, Albert, Albert, Nekrutenko, & Makova, 2006;Ganko et al, 2007;Gu, Zhang, & Huang, 2005;Liu et al, 2015;Wagner, 2002). Here clear divergence in expression patterns was observed among lepidopteran Treh genes ( Figure 3).…”
Section: Discussionmentioning
confidence: 77%